Risk factors of urinary incontinence in women: a literature review. Issue 3 (26th January 2016) - Seshan, Vidya; AlKhasawneh, Esra; Al Hashmi, Iman Hamed
ABSTRACT: The purpose of this literature review is to recapitulate the risk factors and predictors of urinary incontinence (UI) in women identified in different published studies, thereby filling such gap in knowledge. The review identified primary research papers published in peer‐reviewed journals on risk factors and predictors of UI. The search strategy used for collecting the literature was done using PubMed, Google Scholar and CINAHL databases from 2002 to 2012. The full text articles were obtained as part of the second stage selection process, using the pre‐agreed selection criteria. Twelve articles were identified, this includes four cross‐sectional studies, five prospective cohort studies, two co‐relational descriptive studies and one longitudinal study. Majority of these studies concluded that the major risk factors of UI are age, parity, body mass index (BMI), menopause, recurrent UTI, hysterectomy, number of abortions, foetal weight and the comorbid condition such as diabetes, chronic pulmonary disease. Health care providers need to educate women about the risk factors of UI and health‐promoting actions to reduce the risk of UI. Researchers have to enhance primary prevention and promote strategies that help women alter and modify their lifestyle. Lifestyle modification such as healthy food habits, Kegel's exercises and weight reduction ensures the general health promotion and relief from UI symptoms.